Global patterns of diel vertical migration times and velocities from acoustic data. (27th October 2015) - Bianchi, Daniele; Mislan, K. A. S.
Abstract: Diel vertical migrations (DVM) of zooplankton and micronekton are observed throughout the world ocean, where they influence ecological interactions and biogeochemical cycles. Despite their common occurrence, descriptions of the characteristics of these migrations are currently limited at the large scale. We analyze trajectories of migrations from a global dataset of acoustic backscatter to identify the large‐scale patterns of the timing and speed of DVM. Sound scattering layers (SSL) leave the surface 21 ± 20 min before sunrise, and return to it 17 ± 23 min after sunset, while changes in bulk surface backscatter appear to be nearly synchronous to sunrise and sunset. Mean downward migrations (7.6 ± 3.6 cm s −1 ) are significantly faster than mean upward migrations (6.5 ± 3.5 cm s −1 ). Furthermore, coherent and predictable variations of migration properties at the scale of ocean basins are evident. These variations appear to be related to the depths of migration, such that deeper migrations, observed for example in the subtropical gyres, the western tropical Pacific and the Southern Ocean, show earlier departures and later arrivals than shallower migrations. Vertical velocities peak in the tropical and subtropical regions, and decline towards the poles, with the strongest declines observed in the North Pacific. Migration velocities are also correlated to migration depths, with deeper migrations being faster than shallow migrations. These new constraints on the characteristics of migrating SSL could help shed light on the physiological, ecological, and environmental controls that regulate DVM behavior.